Small-bowel capsule endoscopy and device-assisted enteroscopy for diagnosis and treatment of small-bowel disorders: European Society of Gastrointestinal Endoscopy (ESGE) Guideline - Update 2022 - Pennazio, Marco; Rondonotti, Emanuele; Despott, Edward J; Dray, Xavier; Keuchel, Martin; Moreels, Tom; Sanders, David S; Spada, Cristiano; Carretero, Cristina; Cortegoso Valdivia, Pablo; Elli, Luca; Fuccio, Lorenzo; et al. (Endoscopy, 2023)
MR1: ESGE recommends small-bowel capsule endoscopy as the first-line examination, before consideration of other endoscopic and radiological diagnostic tests for suspected small-bowel bleeding, given the excellent safety profile of capsule endoscopy, its patient tolerability, and its potential to visualize the entire small-bowel mucosa.Strong recommendation, moderate quality evidence. MR2: ESGE recommends small-bowel capsule endoscopy in patients with overt suspected small-bowel bleeding as soon as possible after the bleeding episode, ideally within 48 hours, to maximize the diagnostic and subsequent therapeutic yield.Strong recommendation, high quality evidence. MR3: ESGE does not recommend routine second-look endoscopy prior to small-bowel capsule endoscopy in patients with suspected small-bowel bleeding or iron-deficiency anemia.Strong recommendation, low quality evidence. MR4: ESGE recommends conservative management in those patients with suspected small-bowel bleeding and high quality negative small-bowel capsule endoscopy.Strong recommendation, moderate quality evidence. MR5: ESGE recommends device-assisted enteroscopy to confirm and possibly treat lesions identified by small-bowel capsule endoscopy.Strong recommendation, high quality evidence. MR6: ESGE recommends the performance of small-bowel capsule endoscopy as a first-line examination in patients with iron-deficiency anemia when small bowel evaluation is indicated.Strong recommendation, high quality evidence. MR7: ESGE recommends small-bowel capsule endoscopy in patients with suspected Crohn's disease and negative ileocolonoscopy findings as the initial diagnostic modality for investigating the small bowel, in the absence of obstructive symptoms or known bowel stenosis.Strong recommendation, high quality evidence. MR8: ESGE recommends, in patients with unremarkable or nondiagnostic findings from dedicated small-bowel cross-sectional imaging, small-bowel capsule endoscopy as a subsequent investigation if deemed likely to influence patient management.Strong recommendation, low quality evidence. MR9: ESGE recommends, in patients with established Crohn's disease, the use of a patency capsule before small-bowel capsule endoscopy to decrease the capsule retention rate.Strong recommendation, moderate quality evidence. MR10: ESGE recommends device-assisted enteroscopy (DAE) as an alternative to surgery for foreign bodies retained in the small bowel requiring retrieval in patients without acute intestinal obstruction.Strong recommendation, moderate quality evidence. MR11: ESGE recommends DAE-endoscopic retrograde cholangiopancreatography (DAE-ERCP) as a first-line endoscopic approach to treat pancreaticobiliary diseases in patients with surgically altered anatomy (except for Billroth II patients).Strong recommendation, moderate quality evidence.
Keywords: Crohnova nemoc; nemoci střev; kapslová endoskopie; Anemia, Iron-Deficiency; Intestinal Diseases; Humans; Crohn Disease; lidé; gastrointestinální endoskopie; gastrointestinální krvácení; Capsule Endoscopy; Endoscopy, Gastrointestinal; anemie z nedostatku železa; Gastrointestinal Hemorrhage